(2x-1)=3(x+7)

Simple and best practice solution for (2x-1)=3(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-1)=3(x+7) equation:


Simplifying
(2x + -1) = 3(x + 7)

Reorder the terms:
(-1 + 2x) = 3(x + 7)

Remove parenthesis around (-1 + 2x)
-1 + 2x = 3(x + 7)

Reorder the terms:
-1 + 2x = 3(7 + x)
-1 + 2x = (7 * 3 + x * 3)
-1 + 2x = (21 + 3x)

Solving
-1 + 2x = 21 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-1 + 2x + -3x = 21 + 3x + -3x

Combine like terms: 2x + -3x = -1x
-1 + -1x = 21 + 3x + -3x

Combine like terms: 3x + -3x = 0
-1 + -1x = 21 + 0
-1 + -1x = 21

Add '1' to each side of the equation.
-1 + 1 + -1x = 21 + 1

Combine like terms: -1 + 1 = 0
0 + -1x = 21 + 1
-1x = 21 + 1

Combine like terms: 21 + 1 = 22
-1x = 22

Divide each side by '-1'.
x = -22

Simplifying
x = -22

See similar equations:

| 9x+7y+17z=107 | | 4-(15-2x)=3(2x-9-2(9-x)) | | 4x^2-3x+12=0 | | 60x+1=3(3+4x) | | 60x+10=80x-6 | | 36=2l+2w | | -21=7+6(c+5) | | 10x+1=12x-17 | | -6(7-9x)=-21 | | 6.8x=18000+(2x) | | -3+6(1+9v)=-28 | | -270=-5(9x-9) | | x/-12+4=9 | | y/3+18=70 | | 114-9x=-6x-156 | | -31=-6(3d+5) | | -22-3x=54+x | | -9b+5b=34 | | 171+5x=-6x-156 | | 2x-4(3x-3)=92 | | -4(8a+7)=23+5a | | 9x-53=12x+28 | | 51-5x=-63+x | | 0,25(4x-3)=3-x | | -17-6z=-9(7z+8) | | 0,1(4x-3)=3-x | | -3+7n=39forn | | -33=-3n-4n | | 2/3x+1/4=5/6 | | 87=2x-5 | | 10x*y-50000=0 | | 13-2t=4 |

Equations solver categories